Dual inhibitors of DNMT and HDAC remodels the immune microenvironment of colorectal cancer and enhances the efficacy of anti-PD-L1 therapy - Zhanbo Yang; Bizhu Chu; Yao Tu; Lulu Li; Dawei Chen; Shouhui Huang; Wenjun Huang; Weiwen Fan; Qinyuan Li; Cunlong Zhang; Zigao Yuan; Jumin Huang; et al. (Elsevier, 2024)
Colorectal cancer is the second most prevalent and deadly cancer worldwide. The emergence of immune checkpoint therapy has provided a revolutionary strategy for the treatment of solid tumors. However, less than 5 % of colorectal cancer patients respond to immune checkpoint therapy. Thus, it is of great scientific significance to develop "potentiators" for immune checkpoint therapy. In this study, we found that knocking down different DNMT and HDAC isoforms could increase the expression of IFNs in colorectal cancer cells, which can enhance the effectiveness of immune checkpoint therapy. Therefore, the combined inhibition of DNMT and HDAC cloud synergistically enhance the effect of immunotherapy. We found that dual DNMT and HDAC inhibitors C02S could inhibit tumor growth in immunocompetent mice but not in immunocompromised nude mice, which indicates that C02S exerts its antitumor effects through the immune system. Mechanistically, C02S could increase the expression of ERVs, which generated the intracellular levels of dsRNA in tumor cells, and then promotes the expression of IFNs through the RIG-I/MDA5-MAVS signaling pathway. Moreover, C02S increased the immune infiltration of DCs and T cells in microenvironment, and enhanced the efficacy of anti-PD-L1 therapy in MC38 and CT26 mice model. These results confirmed that C02S can activate IFNs through the RIG-I/MDA5-MAVS signaling pathway, remodel the tumor immune microenvironment and enhance the efficacy of immune checkpoint therapy, which provides new evidence and solutions for the development of "potentiator" for colorectal cancer immunotherapy.